2023
DOI: 10.1111/febs.17015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the craniosynostosis‐associated interleukin‐11 receptor variants p.T306_S308dup and p.E364_V368del

Birte Kespohl,
Anna‐Lena Hegele,
Stefan Düsterhöft
et al.

Abstract: Interleukin‐11 (IL‐11) is a member of the IL‐6 family of cytokines and is an important factor for bone homeostasis. IL‐11 binds to and signals via the membrane‐bound IL‐11 receptor (IL‐11R, classic signaling) or soluble forms of the IL‐11R (sIL‐11R, trans‐signaling). Mutations in the IL11RA gene, which encodes the IL‐11R, are associated with craniosynostosis, a human condition in which one or several of the sutures close prematurely, resulting in malformation of the skull. The biological mechanisms of how muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…More recent work showed that this variant of IL-11R transfected into HEK293 cells exhibited retention of IL-11R in the endoplasmic reticulum (ER) due to failure of transport to the cell membrane, and that this may have originated in defective post-translational glycosylation of the receptor [6]. Defective glycosylation and trafficking have been studied in a similar manner and proposed for the recently described IL-11R T306_S308dup variant [7]. Such post-translational modifications occur in the ER and are common to many transmembrane proteins.…”
Section: Multiple Variants In Il-11 Signalling Associated With Cranio...mentioning
confidence: 79%
See 4 more Smart Citations
“…More recent work showed that this variant of IL-11R transfected into HEK293 cells exhibited retention of IL-11R in the endoplasmic reticulum (ER) due to failure of transport to the cell membrane, and that this may have originated in defective post-translational glycosylation of the receptor [6]. Defective glycosylation and trafficking have been studied in a similar manner and proposed for the recently described IL-11R T306_S308dup variant [7]. Such post-translational modifications occur in the ER and are common to many transmembrane proteins.…”
Section: Multiple Variants In Il-11 Signalling Associated With Cranio...mentioning
confidence: 79%
“…Confirming that these most likely relate to loss of function, null mice for IL-11R also exhibit a partially penetrant craniosynostosis phenotype [3,6]. Recent work from Birte Kespohl et al [7] has provided new insights into how some of these variants influence IL-11R function.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations